Heat Transfer in the Ducts of the Cooling Systems of Traction Motors - Ð. Aleksahin, A; V Panchu, A; A. Parkhomenko, L; V. Bilovol, H (International Journal of Engineering and Technology, 2018)
Requirements for increasing thermal efficiency heat exchangers, which lead to energy saving, material and reduction cost, and as a result of reducing the impact on the environment, led to the development and use of various methods of increasing heat transfer. These methods are called intensification of heat transfer processes. Intensification of heat and mass transfer processes is of great importance for making progress in improving the existing and creation of new energy and heat-exchange equipment. Among the ways of intensifying heat transfer, the swirling of flows of working media is one of the simplest and most common methods and is widely used in energy-intensive channels of nuclear power plants, heat exchangers, aeronautical and rocket and space equipment, chemical industry and other technical devices. We have proposed formulas to determine the cooling air velocity necessary to ensure the required temperature condition of the traction motor assemblies. Decrease in the power of fans in the cooling system using the artificial heat transfer intensification in the ducts was estimated based on the generalization of the results of calculations.Â Â